2004
DOI: 10.1080/00050060410001660362
|View full text |Cite
|
Sign up to set email alerts
|

Non-attendance at a university-based psychology clinic: Telephone appointment reminders versus no reminders

Abstract: Previous research has identified non‐attendance in community clinics as a serious problem, especially in terms of viability of these clinics. Yet, the same research offers little clarification about how to combat these non‐attendance rates. The current study was an initiative at the University of South Australia School of Psychology Clinic, which sought to reduce the non‐attendance rate through the use of telephone reminders for appointments in the following week. Reminders were made during alternating weeks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…There was a statistically significant improvement in attendance in this early randomised controlled trial. Similar positive results have since been reported for first attenders by Burgoyne et al (1983), MacDonald et al (2000) and Conduit et al (2004), and for both first attenders and follow-up patients by Shivack & Sullivan (1989) and for follow-up patients by Bamford et al (2004), the latter using both telephone and postal reminders with alcohol misusers. Telephone reminders seem to be particularly effective for elderly patients, especially those with dementia (Dockery et al, 2001).…”
Section: Reminder and Memory Aidssupporting
confidence: 69%
See 1 more Smart Citation
“…There was a statistically significant improvement in attendance in this early randomised controlled trial. Similar positive results have since been reported for first attenders by Burgoyne et al (1983), MacDonald et al (2000) and Conduit et al (2004), and for both first attenders and follow-up patients by Shivack & Sullivan (1989) and for follow-up patients by Bamford et al (2004), the latter using both telephone and postal reminders with alcohol misusers. Telephone reminders seem to be particularly effective for elderly patients, especially those with dementia (Dockery et al, 2001).…”
Section: Reminder and Memory Aidssupporting
confidence: 69%
“…Telephone reminders seem to be particularly effective for elderly patients, especially those with dementia (Dockery et al, 2001). Messages left on an answerphone can also be successful (Conduit et al, 2004). McFall et al (2000) conducted a pilot outreach intervention for combat veterans receiving disability benefits for post-traumatic stress disorder but not receiving treatment.…”
Section: Reminder and Memory Aidsmentioning
confidence: 99%
“…The use of telephone reminders prior to scheduled psychotherapy appointments significantly reduces TR (Kluger & Karras, 1983; Macdonald, Brown & Ellis, 2000), but has no effect on PT (Conduit, Byrne, Court & Stefanovic, 2004). Telephone appointment conformation by the treating therapist does not significantly reduce PT, when compared to matched clerical contact or no contact (Hershorn & Rivas, 1993).…”
Section: Narrative Overview Of Strategies To Promote Psychotherapy Atmentioning
confidence: 99%
“…Both studies asked participants to visualise themselves walking into the therapy centre and talking to their META-ANALYSIS OF PSYCHOTHERAPY ATTENDANCE 6 therapist. Although this strategy significantly reduced TR in the intervention group for Sherman and Anderson (1987), this effect was not replicated by Buckner et al (2009).A commonly employed TR and PT strategy in medical settings is telephone contact prior to appointments (see Macheira, Leon, Rowe, Stephenson & Haynes, 1992, for a meta-analysis).The use of telephone reminders prior to scheduled psychotherapy appointments significantly reduces TR (Kluger & Karras, 1983; Macdonald, Brown & Ellis, 2000), but has no effect on PT (Conduit, Byrne, Court & Stefanovic, 2004). Telephone appointment conformation by the treating therapist does not significantly reduce PT, when compared to matched clerical contact or no contact (Hershorn & Rivas, 1993).…”
mentioning
confidence: 99%
“…18,19,30,31 Nevertheless, even in practices with low baseline no-show rates, the risk of no-show is heterogeneous-that is, some patients are more likely of noshows than others. 9,10,28,29,[32][33][34] Prior work has effectively demonstrated that no-shows are predictable; validated models can accurately predict the likelihood that a patient will fail to keep a scheduled appointment. 9,[35][36][37][38] Subspecialty clinics have made use of the predictability of no-shows by integrating predictive modeling to target interventions to those at high risk of no-show.…”
Section: Introductionmentioning
confidence: 99%